Effect of Supplementary Lenses on logMAR Visual Acuity. - Rosenfield, Mark; Portello, Joan K.; Pereira, Stephen (Optometry & Visual Performance, 2016)
Background: While previous studies have examined the effect of supplementary plus lenses on visual resolution, albeit sometimes using sub-optimal techniques, the effect of overminusing an accommodating patient (adding additional minus lens power) is less clear. This study assessed distance logMAR visual acuity (VA) through plus and minus lenses added to the optimal refractive correction. Methods: The study was performed on 20 subjects. After determining the distance refractive correction, supplementary spherical lenses ranging from +1.00 to -1.00D (in 0.12D steps) were introduced in random order, and logMAR resolution VA was measured through these lenses using Landolt C optotypes at a viewing distance of 4m. Results: As expected, +1.00 and +0.75D lenses produced a significant reduction in VA. However, no significant change was observed for lenses ranging from +0.50 to -1.00D. The mean VA for this range of lenses was -0.14 logMAR (SD=0.10). Within the range from plano to +1.00D, a significant positive linear correlation was observed between VA and supplementary lens power, described by the function logMAR VA = 0.36F - 0.19 (where F = lens power). Conclusion: In accommodating individuals, the effect of supplementary lens power between +1.00 and -1.00D is predictable. Plus lenses produce a linear increase in logMAR VA, with 1D of defocus producing a loss of approximately 3 lines of logMAR acuity, while no significant change in VA was found when minus lenses were added. Previous findings on the effect of fogging lenses as a check for induced hyperopia may have over-estimated the expected reduction in VA.